Hexagonal germanium formed via a pressure‐induced phase transformation of amorphous germanium under controlled nanoindentation. Issue 5 (21st March 2013) - Williams, James S.; Haber, Bianca; Deshmukh, Sarita; Johnson, Brett C.; Malone, Brad D.; Cohen, Marvin L.; Bradby, Jodie E.
Abstract We have studied the stable end phase formed in amorphous germanium (a‐Ge) films that have been subjected to a pressure‐induced phase transformation under indentation loading using a large (20 µm) spherical indenter. After indentation the samples have been annealed at room temperature to remove any residual unstable R8 and BC8 phases. Raman spectroscopy indicates a single broad peak centred around 292 cm–1 and we have used first principles density functional perturbation theory calculations and simulated Raman spectra for nano‐crystalline diamond cubic germanium (DC‐Ge) to help identification of the final phase as hexagonal diamond germanium (HEX‐Ge). Transmission electron microscopy and selected area diffraction analysis confirmed the presence of a dominant HEX‐Ge end phase. These results help explain significant inconsistencies in the literature relating to indentation‐induced phase transitions in DC‐ and a‐Ge. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)